Clinical notes [opportunities and challenges in clinical engineering]. - Grimes, S.L (IEEE Engineering in medicine and biology magazine)
Previously, I published an article that extensively detailed the opportunities and challenges now facing the clinical engineering community. The opportunities largely encompass a broad range of technologies that are either now or soon will be available for application in our industry. These include the mapping of the human genome, advancements in micro- and nanotechnology, an exponential growth in information processing capacity and availability, connectivity of technologies, and the advent of autonomic systems. The challenges were the economic, social, and regulatory forces through which clinical engineers must successfully navigate if they are to help the industry realize the full benefit of the aforementioned technological advances. What must clinical engineering do to remain relevant and an effective player on the healthcare team? The steps that clinical engineers need to take are discussed.